THE EFFECT OF SOCIAL SUPPORT AND SELF-ADJUSTMENT ON STRESS IN PSYCHOLOGY STUDENTS OF UIN IMAM BONJOL PADANG - Husna, Nurul; Azmi, M. Zinul; HSB, Resi Julianti; Amelia, Vina (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study aims to determine the effect of social support and self-adjustment on stress in psychology students at UIN Imam Bonjol Padang. The type of research used in this study is correlational with a quantitative method approach. The regression model of the effect of social support and self-adjustment on academic stress produced a coefficient of 0.012 determination (adjusted R square), indicating that social support contributed 1.2% in explaining variations in psychology student stress. With a t value of 2.61 and sign 0.012 indicates that the relationship between social support and psychology student stress is statistically significant. While self-adjustment produces a coefficient of 0.001 determination (adjusted R square), which shows that self-adjustment contributes very little (only 0.1%) in explaining variations in psychology student stress. Researchers concluded from the results of hypothesis testing that there is a relationship between each independent variable (social support and self-adjustment) and the dependent variable (academic stress). Social Support has a significant influence on academic stress. While self-adjustment provides an insignificant influence on academic stress